One-Pot Approach to Pyrido-4-phenanthridinones by Palladium-Catalyzed Annulation of 4-Quinolones with 2-Bromobenzyl Bromides - Arasakumar, Thangaraj; Shyamsivappan, Selvaraj; Gopalan, Subashini; Ata, Athar; Mohan, Palathurai Subramaniam (Synlett, 2019)
A straightforward approach toward the assembly of phenanthridinone heterocycles has been developed through the palladium-catalyzed N-benzylation/intramolecular coupling reactions of readily prepared 4-quinolones with commercially available 2-bromobenzyl bromide derivatives. The target products were prepared in moderate to good yields, with tolerance of various functional groups.
Keywords: one-pot reaction; palladium catalysis; quinolones; phenanthridinones; polycyclic heterocycles; bromobenzyl bromides